1993
DOI: 10.1046/j.1365-2648.1993.18040602.x
|View full text |Cite
|
Sign up to set email alerts
|

Transcultural nursing: a selective review of the literature, 1985–1991

Abstract: This paper reviews selected work, published in nursing journals between 1985 and 1991, on the subject of transcultural nursing. The papers were selected by the use of a computerized literature search at the Royal College of Nursing library, using the keywords transcultural, multicultural, crosscultural and cultural. The benefits and limitations of such an approach will be discussed along with an introduction to transcultural nursing. The journal papers were then reviewed under eight headings, theory and concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1997
1997
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 65 publications
0
8
0
1
Order By: Relevance
“…Relative to the USA, the role of cultural competency in achieving equity in the UK healthcare service has yet to be fully acknowledged. Concerted steps have been taken in the USA and Australia to develop cultural competency in health care (Wilkins 1993, Campinha‐Bacote 2002, Betancourt et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Relative to the USA, the role of cultural competency in achieving equity in the UK healthcare service has yet to be fully acknowledged. Concerted steps have been taken in the USA and Australia to develop cultural competency in health care (Wilkins 1993, Campinha‐Bacote 2002, Betancourt et al. 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Relative to the USA, the role of cultural competency in achieving equity in the UK healthcare service has yet to be fully acknowledged. Concerted steps have been taken in the USA and Australia to develop cultural competency in health care (Wilkins 1993, Campinha-Bacote 2002, Betancourt et al 2003. A systematic review (Beach et al 2005) showed evidence that cultural competency training for healthcare professionals does improve knowledge, attitudes and skills, but it is not certain whether such training improves equity in service delivery.…”
Section: Lack Of An Equitable Servicementioning
confidence: 99%
“…Além disso, devemos nos perguntar como estas mulheres se sentiam diante da enfermeira procedente de outra classe social? Críticos da Teoria de Leininger acreditam que seu foco na cultura omite variáveis como o gênero e a classe social (23) .…”
Section: Oposição Aos Conceitos De Negociação/acomodaçãounclassified
“…Because most styles of psychotherapy are derived from a white, middle class stance, there have been doubts expressed that therapy can be in any way applicable to non‐Western clients (Flaskerud, 1990; Wilkins, 1993). Also criticised as being culturally unsound is the art of family therapy which has been cited as a mono‐cultural therapy style which does not address the different significance and communication styles families and communities hold in non‐Western societies (Campinha‐Bacote, 1997; Pare, 1995).…”
Section: Culture Treatments and Mental Illnessmentioning
confidence: 99%